Impact of non-thermal plasma seed priming and early development stages of two local Thai Cruciferous plants mustard green and rat-tailed radish on glucosinolates, isothiocyanates, minerals, antioxidant and anticancer activities - Thipphiya KARIRAT; Worachot SAENGHA; Khanit MATRA; Kannika NAKHOWONG; Pimsupa PATTANU; Piyatida KITKAYUN; Theerayut BUBPAMALA; Benjaporn BURANRAT; Sirirat DEESEENTHUM; Teeraporn KATISART; Vijitra LUANG-IN (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Over the past decade, non-thermal plasma (NTP) technology has emerged as a promising tool in the food sector. Cruciferous microgreens are known for their anticancer properties, yet the potential of certain varieties at early developmental stages remains underexplored. This study investigated the effects of NTP treatment on seed priming and plant development at 14, 21, and 28 days in mustard green (MG) (Brassica juncea (L.) Czern) and rat-tailed radish (RTR) (Raphanus sativus var. caudatus), focusing on their bioactive compounds and bioactivities. NTP treatment significantly affects stem length, fresh weight, or dry weight compared to untreated seeds. It also enhanced the production of glucosinolates, isothiocyanates (ITCs), specific minerals, total phenolics, total flavonoids, and biological activities in both plants. MG was found to contain sinigrin, gluconapin, allyl ITC, and 3-butenyl ITC, while RTR contained glucoraphasatin and raphasatin. MG exhibited IC50 values ranging from 16–78 µg/mL in cytotoxicity tests against four cancer cell lines HeLa, HepG2, MCF-7 and HT-29 with enhanced activity from NTP. RTR demonstrated greater effectiveness with IC50 values of 12–60 µg/mL with higher activity from NTP. Both plant extracts especially NTP-treated samples reduced cancer cell survival and proliferation by upregulating pro-apoptotic genes (Bax, caspase-3, and p21) and proteins while downregulating anti-apoptotic and metastatic markers (Bcl-2, MMP-9, MMP-2, and cyclin D1). NTP can enhance the therapeutic bioactivity of young plants, with both MG and RTR at 14 and 21 days of growth, showing the higher potential for anticancer applications.